Feasibility and Acceptability of a Group‐Based Relapse Prevention Program for Liver Transplant Recipients With Alcohol‐Associated Liver - Sasha Deutsch‐Link; Sophia Hurr; Heather Gallagher; Ellen W. Green; Christian S. Hendershot; Marie‐Josee Lynch; Daniel Velez; Hersh Shroff (Clinical Transplantation, 2026)
ABSTRACT Alcohol‐associated liver disease (ALD) has become the leading indication for liver transplantation (LT) in the United States. Contemporary practice has shifted toward broader LT access for medically urgent patients with limited pretransplant abstinence or alcohol use disorder (AUD) treatment experience. These patients require AUD treatment post‐LT; however, standardized treatment protocols in this setting remain limited. In response to this need, our center implemented a virtual monthly group‐based relapse prevention program (RPP) for liver transplant recipients (LTRs) transplanted for ALD. The aim of this quality improvement initiative was to examine the feasibility and acceptability of our program. Sessions were administered virtually by a licensed clinical addiction specialist. We collected data from the electronic health record, patient survey data, and qualitative feedback via a focus group at program completion. Of 46 patients contacted, 41% ( n = 19) completed initial enrollment, and 30% ( n = 14) attended at least one session. The majority of patients (61%) were male and those who enrolled were transplanted more recently (15 versus 26 months post‐LT). Attendance was higher in patients with private insurance and a diagnosis of alcohol‐associated hepatitis. Our program was well‐received overall by participants, as seen in both patient satisfaction scores and qualitative feedback. Although focus group participants felt the program was not essential for maintaining abstinence, largely due to an already established commitment to abstinence, they valued the sense of community and purpose it provided. With rising ALD burden and broader access to urgent LT, structured and accessible posttransplant AUD interventions remain an important and unmet need.